2014
DOI: 10.1371/journal.pone.0088062
|View full text |Cite
|
Sign up to set email alerts
|

Tannins from Hamamelis virginiana Bark Extract: Characterization and Improvement of the Antiviral Efficacy against Influenza A Virus and Human Papillomavirus

Abstract: Antiviral activity has been demonstrated for different tannin-rich plant extracts. Since tannins of different classes and molecular weights are often found together in plant extracts and may differ in their antiviral activity, we have compared the effect against influenza A virus (IAV) of Hamamelis virginiana L. bark extract, fractions enriched in tannins of different molecular weights and individual tannins of defined structures, including pseudotannins. We demonstrate antiviral activity of the bark extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 79 publications
2
82
0
10
Order By: Relevance
“…It is also used orally for bleeding, chronic diarrhea, dysentery, bloody urine, painful joints and persistent coughs (Chung et al, 1998). Antiviral activities have been demonstrated for at least twelve different viruses: influenza virus H3N2, H5N3, herpes simplex virus-1, vesicular stomatitis virus, Sendai virus, Newcastle disease virus, poliovirus, coxsackievirus, adenovirus, rotavirus, feline calicivirus, human papillomavirus, and mouse norovirus (Buzzini et al, 2008; Theisen et al, 2014; Ueda et al, 2013). More importantly, previous studies have shown that hydrolysable tannins, chebulagic acid and punicalagin protect against dengue virus infections (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is also used orally for bleeding, chronic diarrhea, dysentery, bloody urine, painful joints and persistent coughs (Chung et al, 1998). Antiviral activities have been demonstrated for at least twelve different viruses: influenza virus H3N2, H5N3, herpes simplex virus-1, vesicular stomatitis virus, Sendai virus, Newcastle disease virus, poliovirus, coxsackievirus, adenovirus, rotavirus, feline calicivirus, human papillomavirus, and mouse norovirus (Buzzini et al, 2008; Theisen et al, 2014; Ueda et al, 2013). More importantly, previous studies have shown that hydrolysable tannins, chebulagic acid and punicalagin protect against dengue virus infections (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the therapeutic safety of gallic acid was found to be lower than other hydrolysable tannins and pseudotannins. 25 In this study, we found that both of these two compounds indeed exerted anti-influenza A (H1N1) virus replication via significant inhibition of viral RNA synthesis. Meanwhile, catechin and gallic acid were shown to inhibit the growth of pandemic influenza A (H1N1) with EC50 of 18.4 mg/mL and 2.6 mg/mL in MDCK cells, and SI of >5.6 and 8.6, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…24 Theisen et al reported the cytotoxic and antiviral activities against H1N1 virus (H1N1 A/Puerto Rico/8/ 34-NS116-GFP) of gallic acid with CC 50 , EC 50 and SI were 770.5 mM, 50.8 mM, and 15.2 mM, respectively, which differs from the results reported from the present study. 25 This could possibly result from the different viral strains used in experimentation. In addition, the therapeutic safety of gallic acid was found to be lower than other hydrolysable tannins and pseudotannins.…”
Section: Discussionmentioning
confidence: 99%
“…Of the investigated substances high molecular weight tannin inhibited both IAV receptor binding and neuraminidase activity. However, those with low molecular weight tannin inhibited neuraminidase but not hemagglutination [36].…”
Section: Tannins As Antiviralsmentioning
confidence: 89%